2015
DOI: 10.5897/ajar2015.9793
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and impact of early maturing maize varieties on farmers income in Safana Local Government Area of Katsina, Nigeria

Abstract: This paper examined the adoption and impact of early maturing maize varieties on farmers' income in Safana Local Government Area of Katsina State, Nigeria. Using random sampling techniques, 300 maize farmers were selected across 10 communities in the Local Government. Data obtained were analyzed using descriptive statistics, adoption index, double difference method and Z-statistics to estimate impact of early maturing maize varieties on income of farmers. The study divided the respondents into 137 adopters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, policies from the local government and farming pattern arrangements from farmers in maize farming are needed to ensure the need for staple food reserves and to archive farmer income increments [5]. Farmers' income and maize production can be increased by applying integrated crop management using high-yielding and early-maturing varieties of crops [21]. Danso-Abbeam, Ehiakpor [22] reported that policies aimed at providing extension workers with adequate training and tools to spread advanced agricultural technology may increase the revenue of maize producers.…”
Section: Policies Implicationmentioning
confidence: 99%
“…However, policies from the local government and farming pattern arrangements from farmers in maize farming are needed to ensure the need for staple food reserves and to archive farmer income increments [5]. Farmers' income and maize production can be increased by applying integrated crop management using high-yielding and early-maturing varieties of crops [21]. Danso-Abbeam, Ehiakpor [22] reported that policies aimed at providing extension workers with adequate training and tools to spread advanced agricultural technology may increase the revenue of maize producers.…”
Section: Policies Implicationmentioning
confidence: 99%
“…So that, the interests of fulfilling the needs of staple food reserve, as well as the increasing farmers' income can still be achieved. Previous study of [22] revealed that the application of integrated management crop (PTT model) particularly by the utilization of high-yielding and earlymaturing improved maize varieties can increase maize productivity at the farm level and famers' income [23]. Moreover, [23] stated that the policies on extension workers provision with sufficient skill and equipment for disseminating improved agricultural technology could become the potential for raising maize farmers' income.…”
Section: Policy Implicationmentioning
confidence: 99%